Initial Public Offerings: The Relevance of the Market Timing Hypothesis Under Conditions of the Czech Capital Market - Meluzín Tomáš (Journal of Competitiveness, 2011)
Abstract In this article, the authors study the relevance of the market timing hypothesis of going public, which tends to explain the lower post-issue operating performance of Czech initial public offerings. The data collected under the conditions of the Czech capital market are compared with the performance of companies selected from the main European stock exchanges, when they decided to adopt the IPO strategy. Achieving the objective required an empirical survey that involved a collection of accounting data in companies that had completed an initial public offer in the Czech capital market. The data were evaluated by financial performance measures. The comparisons were made using descriptive statistical methods. The research results broaden and deepen the present understanding of the market timing hypothesis in companies going public, particularly in the Czech Republic.